1971
DOI: 10.1037/h0031152
|View full text |Cite
|
Sign up to set email alerts
|

Employee reactions to job characteristics.

Abstract: A conceptual framework specifying the conditions under which jobs will facilitate the development of internal motivation for effective performance was developed and tested. The 5s were 208 employees of a telephone company who worked on 13 different jobs. Primary independent variables were: (a) a measure of strength of desire for the satisfaction of "higher order" needs (e.g., obtaining feelings of accomplishment, personal growth); and (6) descriptions of jobs on four core dimensions (variety, autonomy, task id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
1,175
6
40

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,973 publications
(1,276 citation statements)
references
References 35 publications
55
1,175
6
40
Order By: Relevance
“…Consistent with theories of occupational health and performance (e.g., Hackman & Lawler, 1971;Karasek, 1979), our results indicate that the longitudinal effects of job control on mental health, performance, and job satisfaction are unidirectional. In that, consistent with the findings of De Jonge et al (2001), noted above, we found that none of these three outcomes at Time 1 predicted job control at Time 2.…”
Section: Job Controlsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with theories of occupational health and performance (e.g., Hackman & Lawler, 1971;Karasek, 1979), our results indicate that the longitudinal effects of job control on mental health, performance, and job satisfaction are unidirectional. In that, consistent with the findings of De Jonge et al (2001), noted above, we found that none of these three outcomes at Time 1 predicted job control at Time 2.…”
Section: Job Controlsupporting
confidence: 87%
“…It is interesting, however, that results also showed that acceptance interacts with job control to affect these two outcomes, as hypothesized. This work organization characteristic is one of the most important ones that is identified by occupational health and performance theories (e.g., Emery & Trist, 1960;Frese & Zapf, 1994;Hackman & Lawler, 1971;Karasek, 1979) and the research that investigates them (see Terry & Jimmieson, 1999, for a review). Findings from this study suggested that higher levels of acceptance at Time 1 serve to increase the association between higher levels of job control at Time 1 and better mental health and performance at Time 2.…”
Section: Acceptance and Its Interaction With Job Controlmentioning
confidence: 99%
“…First, we had no objective measures of work characteristics. Researchers have argued and considerable empirical evidence has shown that perceptions of work characteristics reflect objective attributes of work (Frese & Zapf, 1999;Fried & Ferris, 1987;Hackman & Lawler, 1971;Morgeson et al, 2012;Spector, 1992). As such, perceived work environments play a mediating role in the relationship between objective work conditions and outcomes (e.g., Oldham & Hackman, 1981;Rousseau, 1978).…”
Section: Study Strengths Limitations and Future Researchmentioning
confidence: 99%
“…The job characteristics model (Hackman & Lawler, 1971;Hackman & Oldham, 1975;Turner & Lawrence, 1965), the sociotechnical systems approach (e.g., Cherns, 1976;Emery & Trist, 1960), action theory (Frese & Zapf, 1994;Hacker, Skell, & Straub, 1968), the demandscontrol model (Karasek, 1979), and the job design theory of stress (Carayon, 1993) all hypothesize that providing people control over their work serves to improve stress-related outcomes. In line with these theories of work control and employee well-being, Terry and Jimmieson (1999) noted, in their review of this research literature, that there appears to be "consistent evidence" that high levels of worker control are associated with low levels of stressrelated outcomes, including anxiety, psychological distress, burnout, irritability, psychosomatic health complaints, and alcohol consumption (p. 131).…”
Section: Job Control Stress-related Outcomes and Work Reorganizatiomentioning
confidence: 99%